A aplicabilidade e a eficácia dos contratos internacionais de trabalho pela autonomia da vontade - Stuchi, Victor Hugo Nazário (2016)
The choice of the theme of this doctoral thesis - Applicability and Effectiveness of International Labor Contracts by Autonomy of the Will - arose from the conviction that employment relations have become increasingly internationalized and freedom of choice been proven effective for the solution of conflicts. To this end, it analyzed the private international law, through a brief historical foreshortening, general notions and the sources of this branch of law. In addition, it sought to verify the main elements of the Single Contract of Work, by definition, description, morphology and characteristics. The conclusion was the analysis of the International Working Agreement with the analysis of the connection elements of international standards, particularly the Convention of Rome and Mexico and the defense of the principle of freedom of choice as a connecting element of the Working International Contracts